Effects of sprint training with and without weighted vest on speed and repeated sprint ability in male soccer players - Rey, E.; Padron-Cabo, A.; Fernández-Penedo, D. (The Journal of Strength and Conditioning Research, 2017)
The purpose of this study was to assess the effect resisted sprint training using weighted vests (WVs) compared with unresisted sprint (US) training on physical fitness (countermovement jump, 10-m sprint, 30-m sprint, and repeated sprint ability [RSA]) in amateur male soccer players. Nineteen soccer players (age: 23.7 ± 4.5 years; height: 178.3 ± 5.8 cm; body mass: 72.9 ± 5.2 kg) were randomly assigned to a WV (n = 10) or a US (n = 9) group. The intervention program had to be performed 2 times a week over 6 weeks. The only difference between the 2 interventions was that the WV group performed all the sprints with an additional weight of 18.9% ± 2.1% of body mass. Within-group analysis showed significant improvements (p < 0.001) in 10-m and 30-m sprint performances from pretest to posttest in WV (+9.42% and +6.04%) and US (+10.87% and +5.10%). Players in both WV and US also showed significant enhancements in RSA average time (AT), fastest time, and total time from pretest to posttest. Percentage changes in 30-m sprint performance, for both groups combined, had a very large correlation with percentage changes in AT of RSA. In the between-groups analysis, there were no differences between the sprint training groups (WV vs. US) in any variable. In conclusion, the findings of this study indicate that both sprint training methods used seem to be effective to improve soccer-related performance measures, and could be beneficial to players and coaches in field settings.